Survival in infants treated with sebelipase Alfa for lysosomal acid lipase deficiency: an open-label, multicenter, dose-escalation study. Issue 1 (December 2017) - Jones, Simon; Rojas-Caro, Sandra; Quinn, Anthony; Friedman, Mark; Marulkar, Sachin; Ezgu, Fatih; Zaki, Osama; Gargus, J.; Hughes, Joanne; Plantaz, Dominique; Vara, Roshni; Eckert, Stephen; et al.
Abstract Background Infants presenting with lysosomal acid lipase deficiency have marked failure to thrive, diarrhea, massive hepatosplenomegaly, anemia, rapidly progressive liver disease, and death typically in the first 6 months of life; the only available potential treatment has been hematopoietic stem cell transplantation, which is associated with high morbidity and mortality in this population. The study objective was to evaluate safety and efficacy (including survival) of enzyme replacement with sebelipase alfa in infants with lysosomal acid lipase deficiency. This is an ongoing multicenter, open-label, phase 2/3 study conducted in nine countries. The study enrolled infants with growth failure prior to 6 months of age with rapidly progressive lysosomal acid lipase deficiency; they received once-weekly doses of sebelipase alfa initiated at 0.35 mg/kg with intrapatient dose escalation up to 5 mg/kg. The main outcome of interest is survival to 12 months and survival beyond 24 months of age. Results Nine patients were enrolled; median age at baseline was 3.0 months (range 1.1–5.8 months). Sixty-seven percent (exact 95% CI 30%–93%) of sebelipase alfa–treated infants survived to 12 months of age compared with 0% (exact 95% CI 0%–16%) for a historical control group (n = 21). Patients who survived to age 12 months exhibited improvements in weight-for-age, reductions in markers of liver dysfunction and hepatosplenomegaly, and improvements in anemia and gastrointestinal symptoms. Three deaths occurred early (first few months of life), two patients died because of advanced disease, and a third patient died following complications of non-protocol-specified abdominal paracentesis. A fourth death occurred at 15 months of age and was related to other clinical conditions. The five surviving patients have survived to age ≥24 months with continued sebelipase alfa treatment; all have displayed marked improvement in growth parameters and liver function. Serious adverse events considered related to sebelipase alfa were reported in one of the nine infants (infusion reaction: tachycardia, pallor, chills, and pyrexia). Most infusion-associated reactions were mild and non-serious. Conclusion Sebelipase alfa markedly improved survival with substantial clinically meaningful improvements in growth and other key disease manifestations in infants with rapidly progressive lysosomal acid lipase deficiency Trial registration Clinicaltrials.govNCT01371825 . Registered 9 June 2011.